2022
DOI: 10.3389/fenvs.2022.858028
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Mangroves Into Rice Cultivation Alters Functional Soil Microbial Community in Sub-Humid Tropical Paddy Soil

Abstract: Conversion of mangrove vegetation into rice cultivation is considerably enhanced nowadays which adversely affects ecological sustainability. Soil microbial community is one of the key indicators to monitor soil health in mangroves. Studies on the variations in the microbial community within mangroves are plenty, whereas reports in mangrove-converted paddy soils are scarce. Therefore, Biolog® eco-plate-based technique was used in this study to assess soil microbial community in the Bhitarkanika (MB) and Sundarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…However, only a significant positive effect of SOC on MBN was observed in this study, and no significant effect of SOC on MBC was observed. This may be related to differences in soil microbial community structure between sampling seasons and study sites, as soil microorganisms tend to prioritize the use of easily degradable carbon sources under unfavorable conditions for their growth [38]. When sampling, the temperature of the low altitude was 10 • C, whereas the high altitude was 2 • C, which is not conducive to microbial growth.…”
Section: Soil-microorganism Carbon Nitrogen Phosphorus Relationshipmentioning
confidence: 99%
“…However, only a significant positive effect of SOC on MBN was observed in this study, and no significant effect of SOC on MBC was observed. This may be related to differences in soil microbial community structure between sampling seasons and study sites, as soil microorganisms tend to prioritize the use of easily degradable carbon sources under unfavorable conditions for their growth [38]. When sampling, the temperature of the low altitude was 10 • C, whereas the high altitude was 2 • C, which is not conducive to microbial growth.…”
Section: Soil-microorganism Carbon Nitrogen Phosphorus Relationshipmentioning
confidence: 99%
“…The biofertilizers usually contain either a single strain or a combination of strains and species which belong primarily to the genera Pseudomonas, Azospirillum and Bacillus (Zhao et al, 2024) and are applied in the soil, on the leaves or by seeds imbibition (Nosheen et al, 2021). The positive effects of biofertilizers application is towards nutrients supply, microbial activity, changes in the ratio between different microorganisms, organic matter turnover, plant stress alleviation, control of pathogens (Vessey, 2003, Bargaz et al, 2018, Kumar et al, 2022. The biological activity of selected bacteria which are used as biofertilizers constituents usually includes one or more traits such as: nitrogen fixation, phosphorus solubilisation and mobilisation, potassium solubilisation and mobilisation, micronutrients supply and plant-growth promoting properties (Saha et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur-oxidizing bacteria are isolated from different habitats including not only rhizosphere soils but also soil and water as sampled from coal mines; copper ore leaching; and sewage water, biogas slurry, tannery effluent, hydrothermal vents, and crude oil mine soils (Kodama and Watanabe, 2003;Anandham et al, 2005;Vidyalakshmi and Sridar, 2007;Marvi et al, 2016;Sultan and Faisal, 2016;Chaudhary et al, 2017;Meier et al, 2017). Apart from the S oxidation, some of the SOB isolated from different niches have been characterized for other plant growth-promoting attributes like production of IAA, siderophores, ACC deaminase, and antibiotics; solubilization of phosphorus, potassium, and zinc; and inhibition of fungal pathogens (Grayston and Germida, 1991;Veerender et al, 2014;Sajjad et al, 2016;Reddy et al, 2018;Dhiman et al, 2019;Yousef et al, 2019;Kumar et al, 2022). The strains with multiple plant-promoting attributes have been reported to enhance the growth and yield in many crop plants (Grayston and Germida, 1991;Dhiman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%